Analisis Rendahnya Minat Masyarakat Menjadi Nasabah Bank Syariah Desa Mekarsari Kecamatan Kumpeh Kabupaten Muaro Jambi - Ahmad Fatoni; Addiarrahman Addiarrahman; Erwin Saputra Siregar (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
The development of an institution cannot be separated from the role of the community it self. Apart from quality, the institution must also give priority to the community, consumert or customers to maintain the continuity of the institution or argency. The activities of Islamic banking institutions must be carried out as closely as possible in introducing the products and services offered by Islamic banking with the aim of increasing or even increasing public interest and trust. In connection with this research, this thesis aims to determine the lack of public interest in choosing Islamic banking products. This type of research is qualitaive research and the data collection techniques are observation, interviews and documentation. This research involved 30 respondents in Mekar Sari Village, Kumpeh districh, consisting of various professions. From the results of research conducted by researchers, 8 respondents stated that they were interested in Islamic banking , but only 3 respondents had used Islamic banking services, and the remaining 14 respondents were not interested and used conventional banking services, then 8 respondents did not respond because they assumed that Islamic banking and conventional bank are the same. Based on the data analysis from this research, the public understanding of Islamic banking are internal and external factors, including personality, motivation, attitudes, beliefs lifestyle, religion, experience, family, culture, society and service. Of these factors, the most dominant main factors are attitude and belief factors, personality factors and community factors themselves.